A Randomized Clinical Trial Testing a Parenting Intervention Among Afghan and Rohingya Refugees in Malaysia. Issue 3 (27th September 2020) - Shaw, Stacey A.; Ward, Kaitlin P.; Pillai, Veena; Ali, Latifa Mahram; Karim, Hamid
Abstract : Refugee families experience uncertainty and stress when residing in countries of first asylum, such as Malaysia, and may benefit from supportive parenting interventions. In the greater Kuala Lumpur, Malaysia area we piloted an eight‐week parenting program with 79 Rohingya and Afghan mothers in nine separate groups. Participants were randomized to an intervention group or a waitlist control group and those in each arm completed a 3‐month follow‐up assessment. Program content addressed positive discipline, strengthening family relationships, adapting to a new environment, and improving health and emotional well‐being. Measures assessed included child intensity and parenting self‐efficacy from the Child Adjustment and Parent Efficacy Scale; positive parenting, inconsistent discipline, and poor supervision from the Alabama Parenting Questionnaire‐Short Form; family intimacy and family conflict from the Family Functioning Scale, and emotional well‐being from the Refugee Health Screening‐15. Participating in the intervention led to beneficial changes in child intensity, parenting self‐efficacy, family intimacy, family conflict, and emotional distress for the treatment group, and all changes except for emotional distress were maintained over time. However, the intervention did not lead to changes in positive parenting, inconsistent discipline, or poor supervision in the treatment group. Findings point to the potential benefits of parenting programs for refugee communities in transitory settings and contribute to the limited body of literature examining such programs. Resumen: Las familias refugiadas sienten incertidumbre y estrés cuando viven en países de primer asilo, como Malasia, por eso, pueden beneficiarse de intervenciones de apoyo para la crianza. En el área metropolitana de Kuala Lumpur, en la zona de Malasia, hicimos una prueba piloto de un programa de ocho semanas sobre la crianza de los niños con 79 madres afganas y rohinyás en nueve grupos distintos. Se asignó aleatoriamente a los participantes a un grupo de intervención o a un grupo de referencia en lista de espera, y las personas de cada división completaron una evaluación de seguimiento a los tres meses. El contenido del programa abordó la disciplina positiva, el fortalecimiento de las relaciones familiares, la adaptación a un entorno nuevo y la mejora del bienestar emocional y de la salud. Los criterios evaluados fueron la intensidad de los niños y la autoeficacia de los padres de la Escala de Adaptación de los Niños y Eficacia de los Padres (Child Adjustment and Parent Efficacy Scale); la crianza positiva; la disciplina inconstante y la mala supervisión del Cuestionario Breve de Alabama sobre la Crianza (Alabama Parenting Questionnaire‐Short Form); la intimidad familiar y el conflicto familiar de la Escala de Funcionamiento Familiar (Family Functioning Scale), y el bienestar emocional de la Evaluación de Salud de los Refugiados‐15 (Refugee Health Screening‐15). La participación en la intervención condujo a cambios beneficiosos en la intensidad de los niños, la autoeficacia en la crianza, la intimidad familiar, el conflicto familiar y el distrés emocional para el grupo de tratamiento, y todos los cambios, salvo el distrés emocional, se mantuvieron con el tiempo. Sin embargo, la intervención no condujo a cambios en la crianza positiva, ni en la disciplina inconstante, ni en la mala supervisión en el grupo de tratamiento. Los resultados señalan los posibles beneficios de los programas de crianza para las comunidades de refugiados en entornos transitorios y contribuyen al escaso corpus de publicaciones que analizan dichos programas. 摘要: 难民家庭在马来西亚等第一庇护国居住时会经历不确定性和压力，并可能受益于起到支持作用的父母养育干预措施。在马来西亚的大吉隆坡地区，我们对79名罗兴亚和阿富汗母亲进行了为期8周的育儿项目试验。他们被分成9个独立的小组。参与者被随机分为干预组和候补对照组，他们全都完成了为期3个月的随访评估。项目内容涉及积正向管教、加强家庭关系、适应新环境以及改善健康和情绪健康。评估量表包括《儿童适应和父母效能量表》中的儿童强度和父母自我效能感;阿拉巴马养育问题问卷简表包括如下方面：积极的教育，不稳定的教养和不合格的监管;《家庭功能量表》中的家庭亲密和家庭冲突，以及《难民健康筛查‐15》中的情感健康。参与干预后，治疗组在儿童强度、家长养育自我效能感、家庭亲密度、家庭冲突和情绪困扰等方面都出现了有益的变化，而且除了情绪困扰外，所有的变化都能长期保持。然而，干预并没有导致治疗组在积极的教育、不稳定的教养或不合格的监管方面的改变。研究结果指出了过渡期生活环境下为难民社区提供养育项目有潜在好处，并为研究此类方案的有限文献提供了参考。